2002
DOI: 10.1177/096721090201000617
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolic Responses to Deep Hypothermic Total Circulatory Arrest and Retrograde Cerebral Perfusion in an Experimental Model

Abstract: An experimental study was designed to search the effectiveness of retrograde cerebral perfusion which is presently used as cerebral protection method for the surgery of arcus aorta. Twelve dogs were subjected to the study. Six of them were remained in total circulatory arrest at 20 °C for 60 min. Retrograde cerebral perfusion was done again at 20 °C for 1 h for the other six dogs. Tumor necrosis factor (TNF). P-selectin, Intracelluler Adhesion Molecule (ICAM), Creatine Phosphokinase (CPK-BB) and tissue Adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For this reason, retrograde brain perfusion from the SVC is one of the techniques that is still being studied and with successful results in aortic arch surgeries. 27 In addition, it has been shown that brain ischemia and EEG changes occur in possible obstructions in the SVC flow. 28 Dopamine pathways are the most emphasized subject in ADHD physiopathology.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, retrograde brain perfusion from the SVC is one of the techniques that is still being studied and with successful results in aortic arch surgeries. 27 In addition, it has been shown that brain ischemia and EEG changes occur in possible obstructions in the SVC flow. 28 Dopamine pathways are the most emphasized subject in ADHD physiopathology.…”
Section: Discussionmentioning
confidence: 99%